2020
DOI: 10.1186/s12937-020-00566-4
|View full text |Cite
|
Sign up to set email alerts
|

Social circumstances and cultural beliefs influence maternal nutrition, breastfeeding and child feeding practices in South Africa

Abstract: Background: Maternal and child undernutrition remain prevalent in developing countries with 45 and 11% of child deaths linked to poor nutrition and suboptimal breastfeeding, respectively. This also has adverse effects on child growth and development. The study determined maternal dietary diversity, breastfeeding and, infant and young child feeding (IYCF) practices and identified reasons for such behavior in five rural communities in South Africa, in the context of cultural beliefs and social aspects. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 40 publications
1
67
2
1
Order By: Relevance
“…While initiation of breastfeeding was high, there were low rates of EBF among HIV-negative women with introduction of liquids and other foods prior to 3 months [ 72 75 ]. In some instances, weaning occurred as early as 2 months [ 76 ]. HIV-positive women expressed fear of HIV transmission to their infants, as well as school and work commitments as reasons for discontinuation of EBF [ 68 , 77 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…While initiation of breastfeeding was high, there were low rates of EBF among HIV-negative women with introduction of liquids and other foods prior to 3 months [ 72 75 ]. In some instances, weaning occurred as early as 2 months [ 76 ]. HIV-positive women expressed fear of HIV transmission to their infants, as well as school and work commitments as reasons for discontinuation of EBF [ 68 , 77 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…It cannot be disputed that good nutrition is a major determinant of positive pregnancy outcome. The link between poverty and malnutrition during pregnancy has been well established in South Africa [ 69 , 71 ], hence the study focusing on other contributing factors of malnutrition (such as food taboos) has been poorly established. Not much is known on the negative or positive effects of food taboos on pregnancy outcomes of Zulu women.…”
Section: Discussionmentioning
confidence: 99%
“…Not much is known on the negative or positive effects of food taboos on pregnancy outcomes of Zulu women. A study done on Xhosa speaking people in the Eastern Cape, South Africa, also highlighted that cultural beliefs are some of major drivers which influence the eating habits during pregnancy and infant feeding [ 71 ]. It was thus important to evaluate if cultural beliefs also influence dietary intake of pregnant women in other cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The 2015 Millennium Development Goal has reported that one third of all children who are undernourished in the world live in sub-Saharan Africa (SSA) [ 8 ]. In these countries, the adequacy and diversity of diet in most households are affected by poverty, insufficient knowledge, social circumstances, cultural beliefs and practices of caregivers [ 5 , 9 ]. In particular, the relationship between dietary diversity and the nutritional status of preschool children is well-established [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%